Al-Hawā wa Al-Syahwah Fī Al-Qur’ān Al-Karīm: Dirāsah Dalāliyyah - Ahmad Suharto; Pamasa Ardana; Intan Pratiwi Mustikasari; Muhammad Badrun (Universitas Darussalam Gontor, 2024)
There is disagreement among scholars since the word